PERIODONTITIS IN PREGNANCY AS RISK FACTORS OF PREECLAMPSIA : A LITERATURE REVIEW - Nur Fitriyah; Melyana Nurul Widyawati (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Periodontitis may indicate the presence of chronic endotoxin inflammatory disease and cytokines, which are considered as risk factors for systemic diseases such as cardiovascular disease, atherosclerosis, and cerebrovascular ischemia. Maternal periodontitis substitutes a potential microorganism that can penetrate the circulation, directly or indirectly has the capacity to affect the health of the mother and fetus. Preeclampsia is associated with an abnormal maternal cytokine response, such as elevated tumor necrosis tumor (TNF)-α, interleukin (IL)-1 and 6 levels that cause endothelial damage to the placenta. Aims: Reviewing epidemiological associations between periodontitis and preeclampsia Methods: The method used in this paper is literature review. Literature searches were conducted using the electronic databases Science Direct and Google Scholar. Results: Many studies showed that periodontitis is a risk factor for the occurrence of preeclampsia. Periodontal disease is known to cause systemic inflammation early in pregnancy through increased IL-6 mechanism and increased systemic CRP, during pregnancy the increased progesterone hormone causes greater vascular permeability, stimulates the production of prostaglandins that can cause inflammation, and can decrease the regulation of interleukin-6 production that is less resistant to bacterial inflammation. Conclussion: The guidance of maintaining the dental and oral health of pregnant and under-five mothers published by the government can be developed into a strategic and innovative program to increase community interest to regularly check the health of teeth to health facilities.